Sex of an Observer Effects on Adults’ Motor, Cognitive, and Affective Dart-Shooting Performance - Mnif, Maha; Chikh, Soufien; Watelain, Eric; Jarraya, Mohamed (Perceptual and motor skills, 2024)
Men and women are characterized by specific physiological, cerebral and emotional characteristics, as well as by the differing nature of their gestures and behaviors. Here, we examined the effects of an observer’s sex on motor, cognitive and affective behaviors during dart-shooting. We compared men and women’s kinematic and affective parameters when perfoming alone or when performing in the presence of an observer of a different sex. We found a sex effect on motor and cognitive performance in interaction with participants’ emotional states. We observed improved accuracy and reaction time in men compared to women, which we attributed to (a) differences in emotional sensitivities between the two sexes and (b) men’s superiority on precision tasks linked to men’s higher proportion of cerebral white matter. Our findings also suggested a sex difference in the social effect of an observer’s sex on motor and cognitive performance. Although there was no effect on affective aspects of performance, emotional state seemed to interact strongly with this social effect.